Inductive approach in teaching grammar in English - Semonská, Petra (Univerzita Pardubice, 2020)
This bachelor thesis deals with the inductive approach to teaching grammar in English and it is divided into two parts. The inductive approach is based on constructivism and a learner-centred approach, so these terms are first discussed. Next, the learner is examined from the psychological and pedagogical point of view, then teaching grammar and finally the inductive approach to teaching grammar is defined. The practical part is devoted to the lesson planning process and contains a set and description of activities reflecting the features of the inductive approach in teaching grammar in English. The practical part is specifically devoted to activities based on the expected outcomes presented in the School Educational Programme of the selected lower-elementary school in the Czech Republic.
Induktivní přístup k výuce gramatiky v anglickém jazyce
Keywords: inductive approach; constructivism; grammar teaching; learner-centredness; teaching methods; induktivní přístup; konstruktivismus; výuka gramatiky; výuka zaměřená na žáka; výukové metody